Comparison of etching optimization process by taguchi method using minitab and design expert software - Azleen Abu Talib
A design of experiment for high throughput pad etch by reactive ion etch is reported. Design of Experiment (DOE) is a technique for optimizing process which has controllable inputs and measurable outputs. The L9 orthogonal array DOE using Taguchi method is applied for Passivation Module (Pad Etch) to obtain acceptable etch rate and smooth uniformity across the wafer. The data were simulated in two statistical softwares that are "Minitab" and "Design Expert" to obtain the optimum combination of parameters with an acceptable etch rate but reduced costs. The DOE consisted of four major varying parameters, which were RF power, CHF3/CF4 gas ratio, pressure and Argon flow rate. The output results which were determined by etch rate, uniformity and Ttitanium Nitride (TiN) remained, were the successful criteria considered. The dependence of the etch rate on the parameters were also analyze and it was found that the RF power and the CHF3/CF4 gas ratio have stronger influence on the etching rate but less influenced by the pressure and Argon flow rate. Based on the Design Expert and Minitab software results obtained, the recommended parameters for obtaining an optimized etching process were RF power of 1000 W, CHF3/CF4 gas ratio of 30/50, Argon flow of 150 sccm and pressure of 200 mTorr. Meanwhile, the Design Expert software is recommended to perform the optimization process as it has more advantages compared to the Minitab software.